THE PERFORMANCE DIFFERENCES BETWEEN HIGH AND LOW SALES TURNOVER COMMUNITY PHARMACIES - Ni Putu Udayana Antari; Ni Putu Dewi Agustini; Ni Made Dharma Shantini Suena (Universitas Airlangga, 2021)
Background: Pharmacy managers will make various efforts to increase their income. In spite of this, pharmacies that have the same facilities can generate greatly varied incomes.Aims: The purpose of this study was to determine the difference between high sales turnover pharmacies and low sales turnover pharmacies as observed through employee motivation, organizational culture, and patient satisfaction.Methods: This study used an analytical design with a questionnaire and checklist. Consumers were selected using the purposive sampling system to assess patient satisfaction. All employees were sampled to assess work motivation and organizational culture. Data analysis was performed using descriptive, bivariate, and multivariate testing.Results: Direct observation of pharmaceutical services from the two outlets shows that there were differences in the time it takes for pharmacist to retrieve the drug, the time for providing drug information, collecting information from patients, and the type of drug information provided, as well as employee motivation, organizational culture, and patient satisfaction.Conclusion: Services at pharmacies with high sales turnover are different from pharmacies with low sales turnover. Empathy has the greatest effect on sales turnover, followed by reliability, responsiveness, assurance, and tangible dimensions. Outlets that have high sales turnover have better organizational culture and higher employee motivation when compared to outlets that have low sales turnover. Keywords: motivation, organizational culture, patient satisfaction, sales turnover